Unbundling in the Airline Industry : Profitability, Customer Perceptions, and Environmental Impact - Martineau, Paul; Pernica, Karel; Jurek, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates the performance, competitiveness, and customer acceptance of the unbundled business model used by low-cost carriers (LCCs) in the European airline industry. Combining a comprehensive literature review, case studies of Ryanair, EasyJet, and Wizz Air, and primary data analysis based on a survey of over 200 respondents, the study explores how strategic cost structures align with evolving passenger expectations. The findings reveal that while unbundling drives financial efficiency and operational flexibility, it also generates mixed levels of customer satisfaction and loyalty. Demographic factors such as age influence acceptance, but behavioural and perceptual variables play a more decisive role. The thesis concludes that the LCC model remains resilient, yet future competitiveness will depend on how airlines manage value perception, pricing transparency, and differentiated service delivery within a cost-optimized framework.
Vedoucí práce: Karel Pernica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses